Antibacterial Derivatives of Ciprofloxacin to Inhibit Growth of Necrotizing Fasciitis Associated Penicillin Resistant Escherichia coli - Bartzatt, Ronald; Cirillo, Suat L. G.; Cirillo, Jeffrey D. (Journal of Pharmaceutics, 2013)
Escherichia coli (E. coli) is associated with necrotizing fasciitis (type I) and can induce enough damage to tissue causing hypoxia. Three ester derivatives of the broad-spectrum antibiotic ciprofloxacin were placed into bacteria culture simultaneously with the parent ciprofloxacin (drug 1) to ascertain the level of antibacterial activity. The n-propyl (drug 2), n-pentyl (drug 3), and n-octyl (drug 4) esters of ciprofloxacin were synthesized under mixed phase conditions and by microwave excitation. The formation of ester derivatives of ciprofloxacin modified important molecular properties such as Log P and polar surface area which improves tissue penetration, yet preserved strong antibacterial activity. The Log P values for drugs 1, 2, 3, and 4 became −0.701, 0.437, 1.50, and 3.02, respectively. The polar surface areas for drugs 1, 2, 3, and 4 were determined to be 74.6 Angstroms2, 63.6 Angstroms2, 63.6 Angstroms2, and 63.6 Angstroms2, respectively. These values of Log P and polar surface area improved tissue penetration, as indicated by the determination of dermal permeability coefficient (Kp) and subsequently into the superficial fascial layer. All drugs induced greater than 60% bacterial cell death at concentrations less than 1.0 micrograms/milliliter. The ester derivatives of ciprofloxacin showed strong antibacterial activity toward penicillin resistant E. coli.